‘Why on Earth Aren’t You Doing Anything?’: Private and Voluntary Policing of Nightlife in Norway - Hiller Foshaugen, Marina (The British journal of criminology, 2025)
This paper explores the role of private security guards and volunteers from ‘The Night Ravens’, and their contribution to the policing of nightlife in Norway. One of their functions in this context is to ‘observe and report’ if they witness deviant, severe or illegal activity. However, the situations they encounter, and expectations associated with their role, may problematize this intended function. This paper analyses experiences and self-understandings of these actors’ practices and argues that conflicting norms affect their role when policing the nightlife. Through observations and interviews with bouncers and Night Raven volunteers, empirical data shows that their organizational mandate, the situations they encounter and relations to others poses different considerations that potentially create tension regarding their role and agency.